A Study of Cecal Ligation and Puncture-Induced Sepsis in Tissue-Specific Tumor Necrosis Factor Receptor 1-Deficient Mice - Vandewalle, Jolien; Steeland, Sophie; Van Ryckeghem, Sara; Eggermont, Melanie; Van Wonterghem, Elien; Vandenbroucke, Roosmarijn E.; Libert, Claude (Frontiers in Immunology, 2019)
Sepsis is a complex syndrome resulting from a dysregulated immune response to an infection. Due to the high prevalence, morbidity and mortality, there is a lot of interest in understanding pathways that play a role in sepsis, with a focus on the immune system. Tumor necrosis factor (TNF) is a pleiotropic pro-inflammatory cytokine and a master regulator of the immune system but clinical trials with TNF blockers in sepsis have failed to demonstrate significant protection. Since TNF stimulates two different receptors, TNF receptor 1 (TNFR1) and TNFR2, pan-TNF inhibition might be suboptimal since both receptors have opposite functions in polymicrobial sepsis. Therefore, we hypothesized that TNF has a dual role in sepsis, namely a mediating and a protective role, and that protection might be obtained by TNFR1 -specific inhibition. We here confirmed that TNFR1-/- mice are protected in the sterile endotoxemia model, whereas TNFR1 deficiency did not protect in the cecal ligation and puncture (CLP)-induced polymicrobial sepsis model. Since whole body TNFR1 blockage might be deleterious because of the antibacterial function of TNF/TNFR1 signaling, we focused on the potential devastating role of TNF/TNFR1 signaling in specific cell types. We were interested in the gut epithelium, the endothelium and hepatocytes using conditional TNFR1-/- mice, as these cell types are believed to play a role in sepsis. However, none of these conditional knockout mice showed improved survival in the CLP model. We conclude that cell-specific targeting of TNFR1 to these cell types has no therapeutic future in septic peritonitis